2024
DOI: 10.1177/1035719x241236779
|View full text |Cite
|
Sign up to set email alerts
|

Utilising existing data for a pilot social return on investment analysis of the family wellbeing empowerment program: A justification and framework

Clare Nolan,
Rosie Bridge,
Grace Holland
et al.

Abstract: Demand is growing in the public, private, and philanthropic sector for economic and quantifiable outcome data to guide decisions regarding the allocation of resources. This paper explores the challenges and opportunities in economically evaluating an Aboriginal Social and Emotional Wellbeing intervention, emphasising the value of utilising existing data. Driven by local and national Indigenous research priorities, the study involved a pilot Social Return on Investment analysis of the Aboriginal Family Wellbein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For instance, instead of directly funding researchers, Lowitja now supports research user organizations, empowering them through direct funding to invite researchers as partners. Additionally, before initiating conventional research, teams must assess the adequacy of existing knowledge (experiential and research) for the identified research need, emphasizing transparency and minimizing research waste [36].…”
Section: Evidence Cited By Researchers To Support Their Claims Of Res...mentioning
confidence: 99%
“…For instance, instead of directly funding researchers, Lowitja now supports research user organizations, empowering them through direct funding to invite researchers as partners. Additionally, before initiating conventional research, teams must assess the adequacy of existing knowledge (experiential and research) for the identified research need, emphasizing transparency and minimizing research waste [36].…”
Section: Evidence Cited By Researchers To Support Their Claims Of Res...mentioning
confidence: 99%